1998
DOI: 10.1002/(sici)1097-0142(19980815)83:4<712::aid-cncr12>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in surgically treated small cell cervical carcinoma followed by adjuvant chemotherapy

Abstract: BACKGROUND Small cell carcinoma of the uterine cervix is an uncommon tumor associated with high mortality even among patients with early stage disease. The role of adjuvant chemotherapy after surgery has been suggested by regimens used for small cell lung carcinoma. During the years 1980‐1997, 19 cases in which various adjuvant chemotherapies were given after hysterectomy were reported in the literature published in English. METHODS Adjuvant chemotherapy was administered consecutively to 23 patients with Stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
6
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 18 publications
3
53
6
2
Order By: Relevance
“…Thus, the investigation on the treatment of cervical neuroendocrine carcinoma is usually considered based on the clinical data of cervical SCNC, or more generally, of lung SCNC. For cervical SCNC, Chang et al reported superior survival with the adjuvant combination chemotherapy of vincristine, doxorubicin and cyclophosphamide (VAC), or of cisplatin and etoposide (PE) [21]. Lee et al concluded that there was no difference in 5-year survival of cervical SCNC between the adjuvant chemotherapy and the adjuvant chemoradiotherapy [22].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the investigation on the treatment of cervical neuroendocrine carcinoma is usually considered based on the clinical data of cervical SCNC, or more generally, of lung SCNC. For cervical SCNC, Chang et al reported superior survival with the adjuvant combination chemotherapy of vincristine, doxorubicin and cyclophosphamide (VAC), or of cisplatin and etoposide (PE) [21]. Lee et al concluded that there was no difference in 5-year survival of cervical SCNC between the adjuvant chemotherapy and the adjuvant chemoradiotherapy [22].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have recommended adjuvant chemotherapy due to the aggressive behavior of this tumor (Chang et al 1998;Boruta et al 2001); however, it is difficult to perform a large scale randomized controlled study given the rarity of the condition. The Gynecologic Oncology Group attempted to study small cell cervical carcinoma in protocol 66 between 1982 and 1986, but failed to recruit sufficient numbers of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although irradiation improves both the local control and survival rates in SCLC patients (Warde and Payne 1992), chemotherapy has historically been the cornerstone of SCLC management. Chang et al attempted to treat SCCC in a fashion similar to that used in SCLC, and reported a 5-year overall survival (OS) of 68% (n = 28) for patients treated with vincristine, adriamycin, and cyclophosphamide alternating with cisplatin and etoposide (VAC/ PE) compared to 33% (n = 12) for patients who received a regimen consisting of cisplatin, vinblastine, and bleomycin (Chang et al 1998). In another small phase II trial of alternating VAC/PE in early-stage SCCC before hysterectomy, 6 of 7 patients experienced a clinical complete response (CR) (Chang et al 1999).…”
mentioning
confidence: 99%
“…Also, adjuvant chemotherapy provides a significant survival advantage for patients either with or without lymph node metastasis (Gardner, 2011). Chemotherapy regimens are extrapolated from those used in small cell carcinoma of the lung, and are based either on vincristine/adriamycin/ cyclophosphamide (VAC) or cisplatin/etoposide (EP) (Chang, 1998;Boruta, 2001). However, EP regimens are www.ccsenet.org/cco Cancer and Clinical Oncology Vol.…”
Section: Discussionmentioning
confidence: 99%